Evolution of affiliation: patterns of convergence from genomes to behaviour. (22nd July 2019) - Fischer, Eva K.; Nowicki, Jessica P.; O'Connell, Lauren A.
Abstract : Affiliative behaviours have evolved many times across animals. Research on the mechanisms underlying affiliative behaviour demonstrates remarkable convergence across species spanning wide evolutionary distances. Shared mechanisms have been identified with genomic approaches analysing genetic variants and gene expression differences as well as neuroendocrine and molecular approaches exploring the role of hormones and signalling molecules. We review the genomic and neural basis of pair bonding and parental care across diverse taxa to shed light on mechanistic patterns that underpin the convergent evolution of affiliative behaviour. We emphasize that mechanisms underlying convergence in complex phenotypes like affiliation should be evaluated on a continuum, where signatures of convergence may vary across levels of biological organization. In particular, additional comparative studies within and across major vertebrate lineages will be essential in resolving when and why shared neural substrates are repeatedly targeted in the independent evolution of affiliation, and how similar mechanisms are evolutionarily tuned to give rise to species-specific variations in behaviour. This article is part of the theme issue 'Convergent evolution in the genomics era: new insights and directions'.